Performance evaluation of conventional and intelligent controller based shunt active filter - Sangeetha, B; Geetha, K (Proceedings of third International Conference on Computational Intelligence and Information Technology, 2013)
In recent years, shunt active power filters (SAPF) based on a voltage source inverter is developed as a solution to harmonic problems. The proposed work presents a three phase, five level cascaded voltage source inverter based shunt active filter to improve power quality. The SAPF controller is based on instantaneous power theory (d-q theory). The output current of the Voltage Source Inverter (VSI) would track the reference current produced by the d-q algorithm. The Fuzzy PI Controller (FLC) is used to regulate the DC link capacitor voltage The CSFMC-SH PWM technique is used to generate switching signal for multilevel shunt active filter. Simulation results obtained are presented and compared with the conventional PI controller. The proposed method prove effective elimination of harmonics using multilevel filter.